Study of Z Boson Cross Section in pp Collision at s=8.16 TeV - Moon, Dong Ho; Kim, Yongsun (Journal of the Korean Physical Society, 2019)
Differential cross section of Z boson production in proton+proton collision was studied using measurements by CMS, ATLAS and CDF experiments. The correlation between the total cross section of Z bosons and the collision energy was analyzed to test power-law function as the scaling baseline. Based on this study, we also computed the differential cross section as functions of rapidity and transverse momentum in the mid-rapidity region for Z boson production in proton+proton collision at s = 8.16 TeV. The PYTHIA Monte Carlo generator was utilized to compensate for the different colliding system ( p p ¯ ) in CDF experiment, as well as to correct the fiducial acceptance by the detector geometry of ATLAS. We validated our method by computing the cross section at 7 and 8 TeV and then comparing them with the existing results. Our result can provide a useful reference for analyzing Z boson yields in p-Pb collision data at s N N = 8.16 TeV that CMS and ATLAS collaboration took in 2018.